Kualitas Kepemimpinan Guru PAK Menjadi Figur Utama yang Diteladani Peserta Didik - Elfin Warnius Waruwu; Riste Tioma Silaen (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
The leadership quality of a PAK teacher has a major role in shaping the character and behavior of students. This article explores how teachers, especially PAK teachers, become central figures who become role models for students. Teacher leadership in this context is not only limited to administrative or managerial capacity, but also includes moral and ethical dimensions that influence students in various aspects of life. PAK teachers play an important role in guiding students in understanding the values, ethics and attitudes that are considered positive in society. PAK teachers are not just instructors, but role models who are looked up to by students. Therefore, the leadership qualities of Sir teachers must be taken seriously. Traits such as integrity, empathy, fairness, and firmness are the main components in forming teachers as good role models. Teacher behavior, both inside and outside the classroom, influences how students see the world and respond to it. The high leadership quality of PAK teachers has a positive impact on student character development. Teachers inspire students to achieve academic achievements and develop positive attitudes such as discipline, cooperation and responsibility. Kualitas kepemimpinan seorang Guru PAK memiliki peran utama dalam membentuk karakter dan perilaku peserta didik. Artikel ini mengeksplorasi bagaimana guru, khususnya Guru PAK, menjadi figur sentral yang menjadi teladan bagi siswa. Kepemimpinan guru dalam konteks ini bukan hanya terbatas pada kapasitas administratif atau manajerial, tetapi juga mencakup dimensi moral dan etis yang memengaruhi siswa dalam berbagai aspek kehidupan. Guru PAK memainkan peran penting dalam membimbing siswa dalam memahami nilai-nilai, etika, dan sikap yang dianggap positif dalam masyarakat. Guru PAK bukan sekadar instruktur, melainkan model peran yang dijunjung tinggi oleh siswa. Oleh karena itu, kualitas kepemimpinan guru Pak harus diperhatikan dengan serius. Sifat-sifat seperti integritas, empati, keadilan, dan ketegasan adalah komponen utama dalam membentuk guru sebagai teladan yang baik. Perilaku guru, baik di dalam maupun di luar kelas, memengaruhi cara siswa melihat dunia dan meresponnya. Kualitas kepemimpinan guru PAK yang tinggi memiliki dampak positif pada perkembangan karakter siswa. Guru menginspirasi siswa untuk meraih prestasi akademis dan mengembangkan sikap positif seperti disiplin, kerja sama, dan tanggung jawab.